Extraordinary measures in extraordinary times – Public measures in support of the financial sector in the EU and the United States - Stéphanie Marie Stolz; Michael Wedow (European Central Bank (ECB), 2010)
The extensive public support measures for the financial sector have been key for the management of the current financial crisis. This paper gives a detailed description of the measures taken by central banks and governments and attempts a preliminary assessment of the effectiveness of such measures. The geographical focus of the paper is on the European Union (EU) and the United States. The crisis response in both regions has been largely similar in terms of both tools and scope, and monetary policy actions and bank rescue measures have become increasingly intertwined. However, there are important differences, not only between the EU and the United States (e.g. with regard to the involvement of the central bank), but also within the EU (e.g. asset relief schemes).
Keywords: C43; E31; O47; R31; 330; bank rescue measures; public crisis management